A new blue AIEgen based on tetraphenylethene with multiple potential applications in fluorine ion sensors, mechanochromism, and organic light-emitting diodes. (14th February 2018) - Li, Yinghao; Zhuang, Zeyan; Lin, Gengwei; Wang, Zhiming; Shen, Pingchuan; Xiong, Yi; Wang, Bohan; Chen, Shuming; Zhao, Zujin; Tang, Ben Zhong
Abstract : A new blue organoboron AIEgen with multiple potential applications is synthesized and studied. Abstract : In this work, we report a new blue AIEgen, (9, 9-dimethyl-7-(4-(1, 2, 2-triphenylvinyl)phenyl)-9 H -fluoren-2-yl)dimesitylborane (TPE-FB), composed of dimesitylboryl, fluorene and tetraphenylethene (TPE) groups. The thermal stability, electronic structure, optical properties, transient fluorescence decay and electroluminescence of TPE-FB are studied. TPE-FB shows high thermal stability and good aggregation-induced emission (AIE) properties. Due to the presence of the dimesitylboryl group, TPE-FB can interact with fluorine ions to cause a blue-shift in the absorption spectrum and an apparent decrease in the emission spectrum. TPE-FB also exhibits mechanochromic properties, and the fluorescence color of its solid can be reversibly switched between blue and sky-blue by simple grinding and heating (fuming). TPE-FB can function as a light-emitting layer in nondoped sky-blue OLEDs with good performances.